NetLibrary Science and Technology E-book Coverage. - Beth Roberts (Issues in Science and Technology Librarianship)
The article presents information on science and technology electronic-books (e-books) offered by NetLibrary. NetLibrary is a division of OCLC Computer Library Center. About 9% of NetLibrary e-book titles were medicine, 5% were computer science and 4% were technology and engineering subjects according to OCLC content management vice president Rich Rosy. NetLibrary offers several options for subscribing e-books. The interface of NetLibrary has been improved making it easier to use and navigate.